Migration strategies of brown trout (Salmo trutta) in a subarctic river system as revealed by stable isotope analysis. Issue 1 (13th July 2018) - Ruokonen, Timo J.; Kiljunen, Mikko; Erkinaro, Jaakko; Orell, Panu; Sivonen, Olli; Vestola, Eero; Jones, Roger I.
Abstract: We estimated the proportions of anadromous and freshwater‐resident brown trout ( Salmo trutta ) in different parts of the subarctic River Näätämöjoki/Neidenelva system (Finland and Norway) using carbon, nitrogen and hydrogen stable isotope analyses of archived scales as identifiers of migration strategy. Our results showed that carbon stable isotope values were the best predictor of migration strategy. Most individuals fell into two clearly distinct groups representing anadromous (47%) or freshwater‐resident (42%) individuals, but some fish had intermediate carbon values suggesting repeated movement between freshwater and the sea. The proportion of anadromous individuals decreased steadily with distance from the sea forming a spatial continuum in migration strategies which is probably maintained by the combination of several factors such as divergent availability of food resources, variable migration costs and genetic differences. These within‐catchment differences in migration strategies should be taken into account in fisheries management practices.